Pemikiran KH. Abdul Wahid Hasyim Tentang Pendidikan Islam dan Relevansinya Terhadap Pendidikan Islam Kontemporer - Permana, Dian; Siregar, Maragustam; Kusmayadi, Yudi; Firmansyah, Firdaus (Journal of Islamic Education, 2023)
Islamic education is a process of individual formation based on Islamic teachings. In Islamic education we involve the basic basic elements of the Koran and Hadith. Furthermore, changes and developments in Islamic educational institutions among traditionalists are almost never touched upon, although similarities are found between traditional educational institutions and institutions developed by modernists. (first) to find out KH Abdul Wahid Hasim's thoughts on Islamic education and (second is to find out the relevance of KH Abdul Wahid Hasim's thoughts on contemporary Islamic education. qualitative research method with the type of library research and the data was collected using "content analysis".The result is, That KH. Abdul Wahid Hasyim is a figure born in an Islamic boarding school who has moderate thoughts. He is one of the figures who was very instrumental in the policies he implemented when he was Minister of Religion. The aim of education according to him is to create students who have good morals, fear Allah and have the skills to live independently so that they do not become a burden on others. Vice versa. According to him too regarding combining general education and religious education is very relevant to Al-Qur'an education. He also explained that knowledge must be free from narrow religious boundaries or confines, let alone political confines. According to his understanding, Islam teaches humans to learn throughout their lives. KH. Abdul Wahid Hasyim founded the State Islamic College which has now developed into a State Islamic University and can be useful for everyone.